Shi'a movement in Malaysia: a general study - Abdul Majid, Mahmood Zuhdi (s.n, 2012)
This paper aims at providing the readers a general picture of the Shi’a movement in Malaysia. A general picture in the sense that it restrains itself from the theological aspects of the movement; the paper is not interested in whether the movement is deviant or not. Following some raids on several adherents of Shi’ism by the Religious Department of Selangor (JAIS) in 2011, the issue of Malaysian Shi’ites has risen again; they are demanding for religious freedom to exercise their beliefs without exercising any fear in the country. Since the issue is a very sensitive one, even among the Sunni-based country, this article seeks to analyze a trend of their movement in the contemporary context; both political and religious. Thus, the findings in this article will be used to objectively define their movement in the country.